2013
DOI: 10.1016/j.pbb.2013.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acid deficiency does not alter the effects of chronic fluoxetine treatment on central serotonin turnover or behavior in the forced swim test in female rats

Abstract: While translational evidence suggests that long-chain omega-3 fatty acid status is positively associated with the efficacy of selective serotonin reuptake inhibitor drugs, the neurochemical mechanisms mediating this interaction are not known. Here we investigated the effects of dietary omega-3 (n-3) fatty acid insufficiency on the neurochemical and behavioral effects of chronic fluoxetine (FLX) treatment. Female rats were fed diets with (CON, n=56) or without (DEF, n=40) the n-3 fatty acids during peri-adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…In the hippocampus of rat dams we found that fluoxetine, regardless of gestational stress exposure, decreased serotonergic functioning. This work is in line with previous work showing that chronic fluoxetine administration to female rats reduces hippocampal 5-HIAA/5-HT ratios (McNamara et al, 2013) and that sub-chronic exposure to the SSRI sertraline decreases 5-HIAA/5-HT levels in the hippocampus of male rats, regardless of stress exposure (Mikail et al, 2012). These findings highlight that serotonergic metabolism of the hippocampus is particularly sensitive to SSRI treatment during adulthood.…”
Section: Discussionsupporting
confidence: 92%
“…In the hippocampus of rat dams we found that fluoxetine, regardless of gestational stress exposure, decreased serotonergic functioning. This work is in line with previous work showing that chronic fluoxetine administration to female rats reduces hippocampal 5-HIAA/5-HT ratios (McNamara et al, 2013) and that sub-chronic exposure to the SSRI sertraline decreases 5-HIAA/5-HT levels in the hippocampus of male rats, regardless of stress exposure (Mikail et al, 2012). These findings highlight that serotonergic metabolism of the hippocampus is particularly sensitive to SSRI treatment during adulthood.…”
Section: Discussionsupporting
confidence: 92%
“…Quetiapine's half‐life (about 7 h) is identical between rats and humans (Nemeroff et al ., ), and the dose used (10 mg·kg −1 day −1 ) is very similar to the one used in clinical practice (about 600–800 mg day −1 ) (Cerullo and Strakowski, ). Fluoxetine is generally used at 20–60 mg day −1 in patients; in a pharmacokinetic study, a daily dose of 20 mg achieved a mean plasma concentration of about 80 ng·mL −1 (Norman et al ., ); this is in agreement with the mean plasma concentration found in rats after 3 days of treatment with fluoxetine at a dose of 10 mg·kg −1 (McNamara et al ., ). Duloxetine is used in patients at range doses of 30–120 mg day −1 and a pharmacokinetic study showed that, in patients, plasma levels ranged between 5 and 135 ng·mL −1 (mean 53.56 ng·mL −1 ) and plasma levels were significantly correlated with efficacy, but also with signs of anxiety and irritability at the highest concentrations (Volonteri et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, McNamara et al ( 87 ) reported that feeding omega-3 PUFA-suffi cient diets from weaning to adulthood (P21-P90) in female rats had no effect on FST behavior compared with omega-3 PUFA-insuffi cient controls. This suggests that there may be a sex difference in the effect of postweaning omega-3 PUFA supplementation on depressive-like behaviors.…”
Section: Downloaded Frommentioning
confidence: 99%